2007
DOI: 10.1177/0193945906295522
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management Decision Making Among Long-Term Care Physicians and Nurses

Abstract: The purpose of this study is to explore attitudes and beliefs that affect decisions about prescribing and administering pain medications in older adults who live in long-term care (LTC), with a particular emphasis on those with cognitive impairment. At each of the four participating LTC facilities, data were gathered from three separate groups of health care professionals: physicians, registered nurses, and registered practical nurses. Based on grounded theory, a model was developed that highlighted critical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(129 citation statements)
references
References 23 publications
10
115
0
4
Order By: Relevance
“…making strategies for pain management in nursing homes and long term care facilities internationally (Gilmore-Bykovskyi and Bowers, 2013, Kaasalainen et al, 2007). The process of pain assessment and management took place in a context which is reliant on effective communication; where the patient needs to be able to communicate their pain and where there is a nurse available to receive that communication.…”
Section: Discussionmentioning
confidence: 99%
“…making strategies for pain management in nursing homes and long term care facilities internationally (Gilmore-Bykovskyi and Bowers, 2013, Kaasalainen et al, 2007). The process of pain assessment and management took place in a context which is reliant on effective communication; where the patient needs to be able to communicate their pain and where there is a nurse available to receive that communication.…”
Section: Discussionmentioning
confidence: 99%
“…Workload and lack of time have been identified as barriers to optimal pain management practices (Dalton et al, 2001;Kaasalainen et al, 2007;Pack-Mabien et al, 2001;Schafheutle et al, 2001). Kaasalainen et al (2007) explored the decision-making process of physicians and nurses in pain management for older adults with cognitive impairment.…”
Section: Contextual Influencesmentioning
confidence: 99%
“…Kaasalainen et al (2007) explored the decision-making process of physicians and nurses in pain management for older adults with cognitive impairment. The results revealed that nurses were constantly working under immense pressure to meet the demands of their workload and had difficulty including time to adequately assess patients' pain or provide psychosocial support.…”
Section: Contextual Influencesmentioning
confidence: 99%
“…Dette vil kunne føre til økt avhengighet av andre, ensomhet og økt bruk av det offentlige helsetilbudet (15). Det er også avdekket at pasienter underrapporterer smerte og ber heller ikke om hjelp til smertelindring (16 sepersonell gir for lite smertestillende til eldre på grunn av redsel for bivirkninger (17,18). Det er også beskrevet kjønnsforskjeller med hensyn til smerterapportering (19,20) og medikamentbruk (21), hvor eldre kvinner rapporterer mer smerte enn menn og har et høyere forbruk av opioider og sedativer (22).…”
Section: Bakgrunnunclassified
“…Resultatene det her refereres til, gjelder legemiddelhåndtering generelt. Vi mener at resultatene kan overføres til smertebehandling, da barrierene synes å vaere de samme (18). Årsaker til underbehandling av smerte kan også tilskrives at pasientene underrapporterer smerten.…”
Section: Variablerunclassified